State Strategic Planning and Spatial Development in the Siberian Regions - Syssoeva, Natalia; Dets, Igor (Quaestiones Geographicae, 2011)
The paper presents an analysis of the influence of strategic planning projects on the socio-economic development of the Siberian regions of Russia. Zoning for strategic planning is now based on the market principle rather than the production one, as used to be the case during the Soviet period. The dynamics of intra-regional migration flows during the period of implementation of major industrial projects shows an absence of spatial correlation among those processes. The existing institutional framework for regional development does not contribute to the achievement of the main strategic objectives. The economy of the regions remains underinvested and tends towards simplification. An increasing dependence on foreign Asian markets should be taken into account when developing new strategic plans.